2011
DOI: 10.1017/s0007114510005659
|View full text |Cite
|
Sign up to set email alerts
|

Dietary modulation of body composition and insulin sensitivity during catch-up growth in rats: effects of oils rich inn-6 orn-3 PUFA

Abstract: The present study investigates whether excessive fat accumulation and hyperinsulinaemia during catch-up growth on high-fat diets are altered by n-6 and n-3 PUFA derived from oils rich in either linoleic acid (LA), a-linolenic acid (ALA), arachidonic acid (AA) or DHA. It has been shown that, compared with food-restricted rats refed a high-fat (lard) diet low in PUFA, those refed isoenergetically on diets enriched in LA or ALA, independently of the n-6:n-3 ratio, show improved insulin sensitivity, lower fat mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…A previous supplementation trial in postmenopausal women reported that a daily dose of 8 g PUFA (safflower oil) increased lean tissue and reduced trunk fat (48). In accordance, rats isocalorically fed with PUFAs (high in linoleic acid) gained more lean tissue and less fat compared with an SFA-rich diet, in line with similar studies (16,17,49,50). The mechanism behind these observations remains to be determined.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A previous supplementation trial in postmenopausal women reported that a daily dose of 8 g PUFA (safflower oil) increased lean tissue and reduced trunk fat (48). In accordance, rats isocalorically fed with PUFAs (high in linoleic acid) gained more lean tissue and less fat compared with an SFA-rich diet, in line with similar studies (16,17,49,50). The mechanism behind these observations remains to be determined.…”
Section: Discussionsupporting
confidence: 76%
“…In the current study, n-6 PUFAs were investigated, but it is possible that n-3 PUFAs have similar effects on body fat accumulation (50)(51)(52). The amount of sunflower oil used in the current study (;40 g per day) corresponds to about three times the customary intake of linoleic acid in the Swedish population.…”
Section: Discussionmentioning
confidence: 96%
“…Fatty acid analysis of tissues and diet were determined on extracted lipids by automated gas liquid chromatography as previously detailed (20). …”
Section: Methodsmentioning
confidence: 99%
“…In the light of previous findings showing that the phenomenon of catch-up fat and the degree of insulin resistance during refeeding on a high fat (lard) diet can be ameliorated using high fat diets rich in safflower/linseed oil (polyunsaturated fatty acids (PUFA) of omega-6 and omega-3 series) (Dulloo et al, 1995; Yepuri et al, 2011), we investigated here the extent to which these metabolic improvements could be related to the regulation of de novo lipogenesis by these dietary fatty acids. To this end, we investigated here the regulation of the pathway of de novo lipogenesis by the different fatty acids in liver, WAT, and brown adipose tissue (BAT) using a high fat diet, rich in safflower/linseed oil (PUFA diet) or a high fat diet rich in lard (SFA-MUFA diet), given to rats during refeeding after a period of caloric restriction.…”
Section: Introductionmentioning
confidence: 96%